Low Bone Mineral Density, Sedentary Lifestyle, and Depression as Risk Factors for Frailty Syndrome at a Home Care Facility in West Jakarta, Indonesia - Yvonne Suzy Handajani; Jonathan Christianto Subagya; Nelly Tina Widjaja (Althea Medical Journal, 2023)
Background: The life expectancy in Indonesia is increasing. The rising number of the elderly people plays a vital role for a country to achieve development success. However, it has many consequences in the health sector, including a frailty syndrome. This study aimed to explore the association between frailty and related factors.Methods: This cross-sectional study was conducted at a home care facility in West Jakarta between September and October 2019, using a simple random sampling method. Data were analyzed using the chi-square test and multivariate logistic regression. The inclusion criteria were members of the home care aged ≥60 years and had signed a written informed consent.Results: In total, 97 respondents were included. Female gender and bone mineral density (BMD) were associated with frailty syndrome (p=0.018 and p=0.05, respectively). Multivariate logistic regression analysis showed the odds ratio of frailty for the female gender (OR= 3.319; 95% CI 1.045–10.543), low bone mineral density (OR= 4.939; 95% CI 1.516–16.090), depression (OR= 7.622; 95% CI 1.246 – 46.621), and low physical activity (OR = 3.639; 95% CI 1.096 – 12.079).Conclusions: There is a relationship between female gender and bone mineral density with frailty syndrome with the risk factors for frailty syndrome in this study are female gender, low bone mineral density, depression, and low physical activity.